(untitled) (The Journal of Cultural Perspectives, 2025)
This article explores the historical evolution of prostitution in Pakistan, particularly focusing on the post-partition trends of traditional prostitution. Prostitution, one of the earliest professions, has long held a significant role in society, flourishing under social, religious, and political patronage. The study emphasizes the overlooked link between traditional prostitution and performing arts, noting that while prostitution is stigmatized today, it was once widely accepted in South Asia. The profession, especially the red-light areas, historically provided Pakistan with some of its finest artists and singers which contrasts with the current criminalization and state repression of traditional prostitution. Shahi Mohallah, Lahore’s historical red-light district, serves as a central case study. The article highlights the marginalization of residents due to state crackdowns, which displaced sex workers to urban outskirts, leading to the rise of forced prostitution. The research seeks to demonstrate that forced prostitution was not a traditional part of Shahi Mohallah’s sex work culture, which had long been intertwined with performing arts. Through historical analysis and exploratory research, the article aims to provide a broader understanding of the changing dynamics of traditional prostitution in post-colonial Pakistan, exploring how state policies have transformed the industry.